2018
DOI: 10.1111/cbdd.13394
|View full text |Cite
|
Sign up to set email alerts
|

A propeller‐like small molecule as a novel G‐quadruplex DNA binder: The study of fluorescent sensing property and preferential interactions with human telo21 structure

Abstract: A new propeller-like small molecule was synthesized with three terminal amino side groups. The molecule was found to be a selective nucleic acid binder towards telo21 G-quadruplex DNA compared with other representative nucleic acids including single-stranded DNA (dA21), duplex DNA (ds26) and RNA. The fluorescent signal of the molecule upon interaction with telo21 G-quadruplex structure shows remarkable enhancement (F /F = 17.9) while interaction with other nucleic acids shows the signal enhancement which is le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…[26][27][28] Several lutidine derivatives have been utilized for biomolecular investigations: interactions with nucleic acids, proteins, and live-cell imaging applications. [29][30][31][32][33] Considering their lower toxicity, high signal-to-noise ratios, and a knowledge of their biomolecular interactions, we used 2,6-lutidine as a scaffold to target sub-cellular organelles. We systematically varied the substituents by incorporating methyl, benzyl, and polyfluorophenyl motifs: the substitutions contribute to the changes in lipophilicity and biomolecular affinity within the cell.…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28] Several lutidine derivatives have been utilized for biomolecular investigations: interactions with nucleic acids, proteins, and live-cell imaging applications. [29][30][31][32][33] Considering their lower toxicity, high signal-to-noise ratios, and a knowledge of their biomolecular interactions, we used 2,6-lutidine as a scaffold to target sub-cellular organelles. We systematically varied the substituents by incorporating methyl, benzyl, and polyfluorophenyl motifs: the substitutions contribute to the changes in lipophilicity and biomolecular affinity within the cell.…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to probe the crucial factors in rational design of G4-selective ligands, our group has developed several ligand systems. We found that, apart from adopting a planar core molecular fragment to construct G4-ligands, the overall molecular size, 116 symmetry, 117,118 flexibility, 83 and the character of terminal groups [119][120][121][122] may affect the in vitro selectivity of the ligand toward G4-structures against RNA, single-and double-stranded DNA. Our study suggests that some smallsized molecular scaffolds including benzothiazole-benzofuroquinolinium, 123,124 benzothiazole-indolium, 125 1-methylquinolinium, 126 thiazole orange 81,84,127 and benzo[e]indole 128 are good molecular fragments for the design of fluorescent G4-ligands to achieve high discrimination ability, sensitivity and quantum yield targeting certain types of G4s for in vitro sensing and live cell imaging.…”
Section: G4-selective Fluorescent Ligands For Molecular Recognition A...mentioning
confidence: 99%
“…Commentary: Reproducible science, why protocols matter David L. Selwood F I G U R E 1 Detection of exon 2 deletion of AIMP2 based on split a G-quadruplex system, the chemical structure of NMM is shown on the right. Figure taken (Sun et al, 2018) and a second describes a novel fluorescent system for detection of genetic mutations but without using sequencing (Zang, Wang, Zhu, Yao, & Shi, 2018). This system is developed for detection of exon 2 deletion of AIMP2 which is thought to important in some cancers, such as ovarian and lung cancers.…”
Section: O M M E N T a R Ymentioning
confidence: 99%
“…The DNA and RNA system tools category highlights the increasing importance of this area to therapeutics, two papers on G‐quadruplex systems: one from Ning Sun and co‐workers (Wing‐Leung Wong lab.) describing a propeller‐like molecule as a probe (Sun et al., ) and a second describes a novel fluorescent system for detection of genetic mutations but without using sequencing (Zang, Wang, Zhu, Yao, & Shi, ). This system is developed for detection of exon 2 deletion of AIMP2 which is thought to important in some cancers, such as ovarian and lung cancers.…”
mentioning
confidence: 99%